Створення реалістичних світлових ефектів у 3D-системах через використання нейронних мереж для фотонного відображення - Могилевський, Д. І. (ХНУРЕ, 2025)
The creation of realistic lighting effects in 3D systems is crucial for enhancing visual authenticity. This study explores the application of neural networks for photon-based rendering. By leveraging deep learning techniques, the proposed approach improves light simulation accuracy and computational efficiency. Neural networks enable adaptive light propagation, enhancing reflections, refractions, and global illumination. The research demonstrates how AI-driven methods optimize rendering pipelines in real-time environments. The findings contribute to the development of more immersive and visually accurate 3D graphics.
Keywords: фотонне відображення; світловий ефект